Photodynamic therapy with photosensitizer photolon for oral leukoplakia - Yu. P. Istomin; T. P. Artemyeva; D. A. Tzerkovsky (Biomedical Photonics)
The objective – to assess tolerability, safety and immediate results of treatment of patients with oral leukoplakia using photodynamic therapy (PDT) with a photosensitizer photolon. The study included 40 patients (7 men, 33 women) with morphologically verified leukoplakia of the oral mucosa. The average age – 55±14 years. Number of treated foci – 109 (1 to 8). Photolon was administered intravenously at doses of 1.7-2.5 mg/kg. Photoirradiation («UPL PDT», Belarus, λ = 660±5 nm) was performed 2.5-3 h after administration: light exposure dose varied from 25 to 100 J/cm2, power density of 0.07 to 0.32 W/cm2, the duration of one field photoirradiation – from 2 to 13.5 min and according to its linear dimensions. The effectiveness of treatment was assessed 1-2 months after PDT by clinical data. Complete regression of foci recorded in 95% of cases (n=38), partial – in 5% (n=2).The follow-up period varied from 1 to 30 months. Full-epithelialization of the wound defect occurred within the period of 3-6 weeks after treatment. Photodynamic therapy may be recommended for patients with circumscribed or widespread oral leukoplakia as a simple, well-tolerated and effective option. Keywords: photodynamic therapy, photolon, oral leukoplakia.